Role of Span-75 in Determining Prognosis of Non-Thrombolysis Acute Ischemic Stroke Patients - Sutanto, Anyeliria; Simanungkalit, Astra Dea; Yunita, Evelyn; Chandra, Anastasya; Pangestu, Aristo; Tiffani, Pamela (Medicinus, 2020)
Introduction: The SPAN-75 index is a modification of the SPAN-100 index as a prognostic tool in acute ischemic stroke patients. Previous studies were using SPAN index in cases of ischemic stroke patients treated with rTPA and in cases of intracerebral hemorrhage.Aim: To determine the role of the SPAN-75 index as a prognostic scoring in patients with acute ischemic stroke who did not get thrombolysis therapy.Method: The subjects were acute ischemic stroke patients at Siloam Hospitals Lippo Village who were not treated with thrombolysis therapy and had no disability before stroke onset during January to April 2019. Subjects were classified into a positive and negative of SPAN-75 index group. Disability due to stroke was assessed with Modified Rankin Score (mRS) at the time of admission and discharged from the hospital. This prospective study was analyzed by the Kruskal-Wallis test.Result: Forty subjects (average age of 57 years old) consisted of 31 negative and 9 positive of SPAN-75. Based on the Kruskal-Wallis test, the SPAN-75 index was positively associated with a more severe degree of stroke disability at the time of admission (p = 0.002), but not related to the change in the degree of disability when the patient was discharged from the hospital (p = 0.807). Age (p = 0.445) and gender (p = 0.578) had no significant relationship with the degree of disability of acute ischemic stroke.Conclusion: The SPAN-75 index is related to the degree of disability of acute stroke patients at the time of admission.